Analisis Pengaruh Harga Minyak Mentah Dunia, PDB per Kapita, Populasi Urbanisasi, Tarif Listrik Terhadap Konsumsi Energi Indonesia Pada Tahun 1990-2019 - Pohan, Hafni; Lubis, Irsad (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to identify the variables influencing Indonesia's energy usage from 1990 to 2019. Urbanization rate, GDP per capita, world crude oil prices, and power rates are the variables that are taken into consideration.Quantitative research is the methodology employed. The World Bank, the North Sumatra Province's Department of Energy and Mineral Resources, and the PT PLN (Persero) Parent Unit for the North Sumatra Region provided the secondary data used in this study. Time series data from 1990 to 2019 with four independent variables and one dependent variable are used in this study. Multiple linear regression tests are used to select the best model after the data is processed using the Stata14 program. The findings demonstrated that energy prices were significantly harmed by electricity tariffs.